MicroRNA-339-5p down-regulates protein expression of β-site amyloid precursor protein-cleaving enzyme 1 (BACE1) in human primary brain cultures and is reduced in brain tissue specimens of Alzheimer disease subjects - Long, Justin M; Ray, Balmiki; Lahiri, Debomoy K (The Journal of biological chemistry, 2014)
Alzheimer disease (AD) results, in part, from the excess accumulation of the amyloid-β (Aβ) peptide as neuritic plaques in the brain. The short Aβ peptide is derived from the large transmembrane Aβ precursor protein (APP). The rate-limiting step in the production of Aβ from APP is mediated by the β-site APP-cleaving enzyme 1 (BACE1). Dysregulation of BACE1 levels leading to excess Aβ deposition is implicated in sporadic AD. Thus, elucidating the full complement of regulatory pathways that control BACE1 expression is key to identifying novel drug targets central to the Aβ-generating process. MicroRNAs (miRNAs) are expected to participate in this molecular network. Here, we identified a known miRNA, miR-339-5p, as a key contributor to this regulatory network. Two distinct miR-339-5p target sites were predicted in the BACE1 3'-UTR by in silico analyses. Co-transfection of miR-339-5p with a BACE1 3'-UTR reporter construct resulted in significant reduction in reporter expression. Mutation of both target sites eliminated this effect. Delivery of the miR-339-5p mimic also significantly inhibited expression of BACE1 protein in human glioblastoma cells and human primary brain cultures. Delivery of target protectors designed against the miR-339-5p BACE1 3'-UTR target sites in primary human brain cultures significantly elevated BACE1 expression. Finally, miR-339-5p levels were found to be significantly reduced in brain specimens isolated from AD patients as compared with age-matched controls. Therefore, miR-339-5p regulates BACE1 expression in human brain cells and is most likely dysregulated in at least a subset of AD patients making this miRNA a novel drug target.